Autism, hypersensitivity and language ability - Hristo Kyuchukov (East European Journal of Psycholinguistics, 2023)
A study with 36 German participants (divided in 3 age groups: 1 gr. 7-11 years; 2 gr. 12-18 years and 3 gr. 19-50 years) was conducted to test the Polyvagal Theory. Our data analysis evaluated a therapeutic intervention using the so-called SSP (Safe and Sound Protocol) developed by Stephen Porges. Frequency modulated music stimulates the parasympathetic vagus nerve with an (musical) input process evaluated by the brain as socially-communicatively salient (musical signals with enhanced prosodic characteristics of human voices). Thus, acoustical processes of (musical) perception become available to the brain's assessment of social signals via the neurophysiology of the ANS. This, in turn, allows for internally processed signals of social safety, resulting in a reduced sense of stress from external sensory inputs. The SSP aims to generally reduce sensory hypersensitivity by stimulating the vagus nerve via the middle ear – and thus, to contribute to a better capacity of (down)-regulating sensory hypersensitivity. In the current study, we demonstrated that participants with ASD showed reduced hyper-sensitivity (visual, auditory, tactile and digestive) after using the SSP. In a second data analysis, we tested the overall impact of language ability and the influence on hyper sensory sensitivity in the autism spectrum. It seems that language ability in general already leads to better regulation and integration of sensory inputs via cognitive-linguistic processing in cortex areas: if a strong sensory stimulus can be assigned and evaluated linguistically, the strength of the stimulus is adjusted thereby. Conversely, different language abilities did not result in a more effective response to the SSP. Since the SSP amplifies prosodic elements of human speech in a characteristic way, the effect of reduced sensitivity to stimuli seems to be due to the autonomic response to paraverbal signals. The results are statistically analyzed using ANOVA.